Origins of the Iberomaurusian in NW Africa: new AMS radiocarbon dating of the Middle and Later Stone Age deposits at Taforalt Cave, Morocco. - Barton, R; Bouzouggar, A; Hogue, J; Lee, S; Collcutt, SN; Ditchfield, P (Elsevier, 2013)
Recent genetic studies based on the distribution of mtDNA of haplogroup U6 have led to subtly different theories regarding the arrival of modern human populations in North Africa. One proposes that groups of the proto-U6 lineage spread from the Near East to North Africa around 40-45 ka (thousands of years ago), followed by some degree of regional continuity. Another envisages a westward human migration from the Near East, followed by further demographic expansion at ∼22 ka centred on the Maghreb and associated with a microlithic bladelet culture known as the Iberomaurusian. In evaluating these theories, we report on the results of new work on the Middle (MSA) and Later Stone (LSA) Age deposits at Taforalt Cave in Morocco. We present 54 AMS radiocarbon dates on bone and charcoals from a sequence of late MSA and LSA occupation levels of the cave. Using Bayesian modelling we show that an MSA non-Levallois flake industry was present until ∼24.5 ka Cal BP (calibrated years before present), followed by a gap in occupation and the subsequent appearance of an LSA Iberomaurusian industry from at least 21,160 Cal BP. The new dating offers fresh light on theories of continuity versus replacement of populations as presented by the genetic evidence. We examine the implications of these data for interpreting the first appearance of the LSA in the Maghreb and providing comparisons with other dated early blade and bladelet industries in North Africa.